C-doped TiO2 nanotubes with pulsed laser deposited Bi2O3 films for photovoltaic application. Issue 4 (15th February 2022) - Bjelajac, Andjelika; Petrović, Rada; Stan, George E.; Socol, Gabriel; Mihailescu, Andreea; Mihailescu, Ion N.; Veltruska, Katerina; Matolin, Vladimir; Siketić, Zdravko; Provatas, George; Jakšić, Milko; Janaćković, Djordje
Abstract: Anodization was used to obtain a nanotubular TiO2 photoanode on F–SnO2 glass. Subsequent annealing in the CH4 atmosphere promoted the C-doping and improved the crystallinity of the TiO2 nanotubes. The pulsed laser deposition was applied to cover the nanotubes with Bi2 O3, serving as a hole transport material. X-ray photoelectron spectroscopy analyses of the doped samples reveal a shift in the valence band's maximum position towards lower binding energy as compared to those observed for the undoped samples (annealed in the air). The doping positively affects the absorption by shifting the absorption edge to 567 nm. I – V measurements under illumination show that the C-doping of TiO2 increases the current density following the absorbance results. The highest open circuit voltage was reached for the samples with the 300 °C-deposited Bi2 O3 layer, pointing to better quality of the p-n junction, hence of the contact between Bi2 O3 and TiO2 . This in situ annealing provided the formation of close contact between Bi2 O3 and TiO2, which enabled a faster charge transport as compared to the contact obtained with no annealing or even with post annealing. Graphical abstract: Image 1 Highlights: C-doping of anodized TiO2 NTs supported on FTO by annealing in CH4 . PLD to cover TiO2 NTs with Bi2 O3 film, serving as a hole transport material. XPS: Shift of VBM to lower BE for the doped vs. the undoped NTs (annealed in air). DRS: Absorption red shift from 430 nm (undoped NTs) to 567 nm (doped NTs). Best PV performances: C-doped TiO2 with Bi2 O3 deposited at 300 °C in situ .